Modellierung und Optimierung der strömungstechnischen Vorgänge in Abweiseradsichtern - Betz, Michael (KIT Scientific Publishing, 2022)
Centrifugal classifiers are processing machines used in the gas-particle classification. The aim of this work is to reduce energy costs by improving the classification properties and reducing the pressure drop. In addition to design measures, the focus is also on model development. For the development of the models, a deeper understanding of the flow processes is required.